2011
DOI: 10.1108/13552551111107525
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics and strategic orientation: entrepreneurs in Canadian manufacturing companies

Abstract: PurposeExtant theories suggest that entrepreneurs' personal characteristics have substantial impacts on their firm's performance. From a resource‐based view, the paper considers an entrepreneur's personal characteristics to be a unique resource endowment to their firm. The paper seeks to discuss these issues.Design/methodology/approachData were collected through a national survey of owners and senior managers of small‐ to medium‐sized Canadian manufacturing companies. Mediation relationships were tested with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 92 publications
2
64
1
7
Order By: Relevance
“…In terms of thinking (cognition) it has been said that entrepreneurs with a high need for cognition (NFC) are more effective at adaptive decision making. 13 The latter is particularly important when the entrepreneur is operating in a fluid, rapidly changing, environment, such as the UK health system.…”
Section: Characteristics Of the Dentist As Entrepreneurmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of thinking (cognition) it has been said that entrepreneurs with a high need for cognition (NFC) are more effective at adaptive decision making. 13 The latter is particularly important when the entrepreneur is operating in a fluid, rapidly changing, environment, such as the UK health system.…”
Section: Characteristics Of the Dentist As Entrepreneurmentioning
confidence: 99%
“…It has been suggested that market-oriented organisations need an organisational culture that facilitates all activities involved with collecting data about customers and competitors in the target market and ensuring this is disseminated throughout the organisation. 13 Along similar lines, the competing values approach to culture describes a developmental culture as a 'dynamic, entrepreneurial, and creative place to work. People are encouraged to take risks and to focus on innovation and individual initiative and freedom.…”
Section: Opinionmentioning
confidence: 99%
“…As explained by Zhang and Bruning (2011), a consensus of previous studies proved a positive relationship between the manager's need for achievement and firm performance. A number of other studies also researched the effect of this construct on firm strategies.…”
Section: Need For Achievement (Nfa)mentioning
confidence: 99%
“…The evidences also revealed that entrepreneurs and managers with high level of need for cognition are more successful at adaptive decision-making (Levin et al, 2000). Nonetheless, the need for cognition has not been examined extensively in the fields of entrepreneurship and strategic management (Zhang and Bruning, 2011;Levin et al, 2000).…”
Section: Need For Cognition (Nfc)mentioning
confidence: 99%
“…Efforts to protect their children, parents deliberately send their children to school on a path they deem much more needed in government or to become employees [5]. Actually, Successful entrepreneurs are also motivated by other personality characteristics such as need for achievement, need for cognition, and internal locus of control [6], leadership ability [7] and a connection to support networks [8].…”
Section: Introductionmentioning
confidence: 99%